Interspecific vulnerabilities to elevated pCO2 in the northwestern Gulf of Mexico, a baseline of sensitivity and geochemical regimes - Armstrong, David A.; Yin, Hang; Hampton, Autumn R.; Hu, Xinping; McFarlin, Kelly M.; Bahr, Keisha D. (Frontiers in Marine Science, 2025)
Marine organisms rely on stable seawater conditions and vary in taxa-specific tolerances to environmental change. The capacity for acclimatization in marine taxa is dependent on local adaptation. Our ability to generate accurate global predictions starts in identifying regional responses, informing facets that fit globally in a mosaic of response to environmental extremes. The northwestern Gulf of Mexico (nwGoM) has not previously been isolated as a region with significant multi-taxon level comparisons under geochemical extremes. Therefore, we aim to procure a nwGoM regional baseline via a literature search in all known marine taxa’s response to elevated CO2 partial pressure (pCO2) coupled with real-time ecosystem modeling of this region. The baseline carbonate chemistry conditions indicate that pH, aragonite saturation state (Ωarag), and pCO2 exhibit greater temporal and spatial variability within the upper 20 m of the water column, with nearshore waters showing more pronounced seasonal spatial variation than offshore waters. Of the taxon reported, 68.5% reported a negative response to increased pCO2, whereas 31.4% showed a neutral or mixed neutral response (positive or negative). Only 11.4% of reported taxa showed a positive response to elevated pCO2. Shown here is a holistic negative response to increased pCO2 through collating external studies. Data was only found on 1.0% of the total species we recorded in the nwGoM region, highlighting a significant gap in our understanding of regional ecosystem wide sensitivity. Of the species shown here, 83% have habitat ranges within the top 20 m of the water column, and with seasonal variability they may be exposed to several extremes, modeled here but overlooked when compared to global predictions. Continuing experimental work on the reported species here will inform regional predictions to fit the global mosaic predicting the state of our oceans to future conditions.